Improving Binaural Ambisonics Decoding by Spherical Harmonics Domain Tapering and Coloration Compensation - Hold, Christoph; Gamper, Hannes; Pulkki, Ville; Raghuvanshi, Nikunj; Tashev, Ivan (Proc. IEEE International Conference on Acoustics, Speech, and Signal Processing (ICASSP), 2019)
A powerful and flexible approach to record or encode a spatial sound scene is through spherical harmonics (SHs), or Ambisonics. An SH-encoded scene can be rendered binaurally by applying SH-encoded head-related transfer functions (HRTFs). Limitations of the recording equipment or computational constraints dictate the spatial reproduction accuracy, thus rendering might suffer from spatial degradation as well as coloration. This paper studies the effect of tapering the SH representation of a binaurally rendered sound field in conjunction with its spectral equalization. The proposed approach is shown to reduce coloration and thus improves perceived audio quality. Sample code is available here. a)b) Figure: a) coloration estimation of third order HRIR reconstruction above 2.5 kHz for impulse responses moving around the listener in ten degree steps in the horizontal plane (θ = 90°); b) cross section (θ = 90 deg) of a spatial dirac pulse magnitude in dB, reconstruction with N = 5 at Ω = [90 deg, 90 deg], and with additional Hann tapering function of SH coefficients as in (8).